Suomen kaan-liitteen alkuperä - Räisänen, Alpo (Kotikielen Seura, 1996)
The origin of the Finnish enclitic particle -kaan (englanti)3/1996 (100)Alpo Risnen (University of Joensuu)THE ORIGIN OF THE FINNISH ENCLITIC PARTICLE -kAAn The Finnish enclitic particle -kin (e.g. poikakin 'a/the boy too, even a/the boy') has a variant form, -kaan/-kn, which is used in negative clauses (e.g. poikakaan '(not) even a/the boy'). In the majority of the other Baltic-Finnic languages, the particle -kin is used in both positive and negative clauses. A negative variant occurs only in Izhorian (-kaa/-k) and in White Sea Karelian (metathesized as -kana/-kn); in the rest of Karelian -kin is usually used in both contexts. Geographical considerations would thus suggest that -kAAn has developed during the separate development of Finnish.The received view assumes that -kAAn was originally a compound suffix: the kA is the same suffix that occurs in the interrogative pronouns kuka 'who?' and mik 'which (one)?' and the final part developed from the enclitic particle -hAn (a marker of given or assumed information). The particle -kAAn is assumed to have developed from -kAhan/ -gAhAn, the weak consonant occurring after a vowel in an unstressed syllable, according to suffixival consonant gradation (a feature of Late Proto-Finnic) (Hakulinen 1979: 237; Mkel 1993: 10).This article puts forward an explanation that differs in part from the received one. This explanation rests, firstly, on the observation that northern Finnish dialects did not originally contain an intervocalic h, in spite of the fact that it generally occurs in these dialects (Mantila 1992: 64-67). Secondly, it is argued that the -kAAn particle in the eastern Finnish dialects originally contained an intervocalic h. The long vowel AA which resulted from the loss of the voiced fricatives "g" and "d" in non-initial syllables has not been preserved in the Savo dialects: e.g. *antaga- > central Savo antoo = standard Finnish antakaa 'give (2. pl. imp. )', *kertada > kertoo = standard kertaa 'time (partitive sing.)'. However, AA has been preserved in the ...